Wetlands and mosquitoes: a review - Dale, P. E. R; Knight, J. M (Wetlands ecology and management, 2008)
This review brings together information on mosquitoes, the diseases they transmit and the wetlands that provide habitats for the immature stages (eggs and larvae). Wetland values are mentioned, though the main literature on this does not generally overlap the mosquito issue. Mosquito management is overviewed to include: the use of larvicides, source reduction in intertidal wetlands and management in freshwater systems. There is not a great deal of information on mosquitoes and freshwater systems, except for constructed wetlands and they are considered separately. We then consider restoration mainly in the context of wetlands that have been the subject of habitat modification for mosquito control. Land use and climate change, as they affect mosquitoes and the diseases they transmit, are also reviewed, as this will affect wetlands via management activities. Finally the review addresses the critical issue of balancing health, both human and environmental, in an adaptive framework. It concludes that there is a need to ensure that both mosquito and wetland management communicate and integrate to sustain wetland and human health.